Развитие одаренности старшеклассников в условиях профильного филологического обучения - Подлевская, Неля В. (International Dialogues on Education Journal, 2017)
In the modern reform of education (образование) the question is crucial for one of the most important tasks of specialized education (обучение) is one of the main tasks of comprehensive schooling in Ukraine – that of personality formation and development based on individual characteristics of students, their educational needs, cognitive interests, abilities and aptitudes, in connection with future occupational directions. Senior students with philological specialisation are taught on the basis of a communicative-cognitive approach, which provides in-depth knowledge of language phenomena and develops communicative abilities and skills. The development of gifted students’ potential is the most important task of the current education system. However, the giftedness of a senior student should be considered as an inclination toward a certain occupation or to building healthy relationships in society, rather than only as a high level of particular knowledge or activities. The important components of such a system are: the particular orientation of the conception of giftedness and specialized education; the identification of the level of giftedness and aptitude for the philological sciences; the assessment of the framework for giftedness development, the design of techniques and methods for teaching and learning, as well as the nurturing of the creative potential of senior students with philological aptitudes for their further self-realization during their philology studies and their practical work as philologists.